IMPLEMENTATION OF DIVERSION TOWARDS CHILDREN WHO COMMIT CRIMINAL ACTS OF DRUG ABUSE IN DENPASAR CITY RESORT POLICE - I Komang Pandu Tanaya; Ni Wayan Ella Apryani (Transpublika Publisher, 2023)
This study aims to determine the application of diversion for children who commit narcotics abuse in the Denpasar City Police, as well as to identify the obstacles encountered in carrying out diversion related to cases of narcotics abuse crimes committed by children in the same jurisdiction. The research method used is empirical legal research by analyzing the gaps between